2018
DOI: 10.1016/j.socscimed.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

“Ne nnipadua mmpe” (the body hates it): Exploring the lived experience of food allergy in Sub-Saharan Africa

Abstract: Allergic diseases have closely followed the rise of non-communicable diseases (NCDs) especially in western societies. As prevalence of NCD is increasing in sub-Saharan Africa (SSA), researchers are hinting that the same future may hold for (food) allergic disease in this world region. Already, researchers are beginning to record prevalence, though with little attention to the social experience of individuals and parents with food allergic children. This paper presents the first qualitative analysis of the dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Qualitative studies on severe FA suggested that parents felt a need to have control of their child's everyday life and described a feeling of constantly being on guard. Insufficient knowledge of FA and anaphylaxis in preschool/school has been identified as a potential cause of anxiety . Some parents were worried their anxiety would affect the child.…”
Section: Results From the Selected Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies on severe FA suggested that parents felt a need to have control of their child's everyday life and described a feeling of constantly being on guard. Insufficient knowledge of FA and anaphylaxis in preschool/school has been identified as a potential cause of anxiety . Some parents were worried their anxiety would affect the child.…”
Section: Results From the Selected Literaturementioning
confidence: 99%
“…Insufficient knowledge of FA and anaphylaxis in preschool/school has been identified as a potential cause of anxiety. [68][69][70] Some parents were worried their anxiety would affect the child. Parents were aware that as the child got older, they would have to learn how to let go, but extending safety zones was associated with much concern and anxiety.…”
Section: Anxiety In Parents and Caregiversmentioning
confidence: 99%
“…Clinicians should inform patients on how to deal with their food allergies. Patients and their parents must be educated on FA in terms of natural history (which is related to the type of food allergen involved), management including prevention of accidental exposure, and rescue therapy in the event of adverse reaction 164 , 165 …”
Section: Management Issues With Respect To Local Circumstancesmentioning
confidence: 99%
“…The perception and experience of risk have been shown to be inherently relational in food allergy experiences. 13,43,45,[47][48][49][50][51][53][54][55][56][58][59][60][61] For example, DeSoucey and Waggoner 48 have argued that there are several different food allergy 'risk frames' that collide in shared spaces. 52 These include different proximity to, and understanding of, risk exposure; different understandings and positioning in relation to 'responsible sociality', which they define as 'an ethic of discernible empathy for proximate others and of consideration of public benefit in social and communal settings' (p51) 48 ; and different ideas of what constitutes 'liberty', for example, having the freedom to fully participate in social life, or being able to act and eat in any way one pleases regardless of others.…”
Section: The Relationality Of Riskmentioning
confidence: 99%
“…111 The anthropological and sociological research thus far has typically explored food allergy experiences and gender through the context of motherhood, with the focus being primarily on the higher burden on women resulting from gendered dynamics of household labour and childcare in different cultural contexts, 65,67,68,70,90 or on concerns about potential impact on their jobs. 45 Food allergy treatments, such as that of Palforzia and other OIT programmes, have also been shown to put a considerable (gendered) burden on mothers due to the time and skill needed to dose and monitor each day at home. 65,68 The gendered dynamics of advocacy work and living with food allergy and the ways in which care is political have also been discussed.…”
Section: Gender Mothering Advocacy and Emotionsmentioning
confidence: 99%